PENGENALAN PEMASARAN RAMAH LINGKUNGAN PADA UKM - Rodhiah; Venky Lukito; Zenita Dian Mahanani (JOURNAL OF SUSTAINABLE COMMUNITY SERVICE, 2023)
Marketing based on environmental sustainability "environmental marketing" is a new development in the field of marketing, and is a potential and strategic opportunity that has a multiplier effect on both business people and society as users. The purpose of PKM activities is to introduce partners to environmentally friendly marketing, the reality in the field shows that SMEs who are partners of activities lack knowledge of environmentally friendly marketing. For this reason, this activity is important to be carried out by the PKM Team in overcoming the problems faced by partners. The partner chosen in this activity is a handicraft business made from shells, processed into various creative products such as flowers, lamps and other decorative decorations. The partner location is in the city of Serang Banten. The methods offered in this activity include training in the form of socialization of the importance of being environmentally friendly in running a business. Conducted online, through zoom meetings. The results of the activity show that it has been able to provide understanding to partners to always pay attention to environmentally friendly marketing which has an effect on competitive advantage.